The unbreakable learner: forging resilience on the path of lifelong growth - Mohd Nasir, Hazira; Mohd Nasir, Nadia (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s age of limitless access to information, the opportunities for lifelong learning are greater than ever, yet true progress depends less on intelligence or resources than on resilience—the ability to face failure, confusion, and the inevitable slowdown that follows the initial “beginner’s boost.” While early learning often feels exciting and fast, every learner eventually encounters the “dip,” a stage where progress stalls, challenges intensify, and motivation wavers. This is the critical point at which many give up, but resilient learners persist, accepting temporary difficulty as part of the process rather than a sign of inadequacy.